The experience of leaving a valuable object: An investigation of emotional processes related to Hoarding disorder features. - Susanna Pardini; Silvia Olivetto; Francesca Fusina; Caterina Novara (PLoS ONE, 2023)
One of the core features of hoarding is a significant resistance to discarding objects, which is fueled by dysfunctional beliefs and unwarranted negative emotions that hoarders tend to feel when disposing of their possessions. To our knowledge, longitudinal studies investigating the psychological effects that people who hoard experience after separating from their valuable possessions have yet to be conducted. Our study's principal aim was to explore psychological processes that individuals with high hoarding features (n = 53; 49.1%) and individuals with low hoarding features (n = 55; 50.9%) experienced when they had to separate from a valuable possession. To do this, we evaluated participants' thoughts and feelings at several time points after they had to leave a valuable object at the University laboratory (evaluations were specifically conducted at baseline, during the week, and at the end of the week). To investigate hoarding and anxiety, as well as depressive, obsessive-compulsive, and emotional processes-related features, a mixed-method approach was employed involving self-report questionnaires, ad hoc surveys, and a daily self-monitoring schedule. Our findings showed that compared to participants with low hoarding features, participants with high hoarding traits: 1) scored higher for anxiety sensitivity, distress tolerance, and emotional dysregulation; 2) reported having more negative emotions when leaving their object; 3) had more intrusive object-related beliefs; and 4) experienced a higher frequency of negative emotions as well as a higher level of distress during the week. Both groups experienced more negative emotions in the first part of the week, which decreased as the time at which participants could receive their object back drew closer. Finally, dysfunctional beliefs about leaving a personal object (Saving Cognitions Inventory), sensitivity to anxiety (Anxiety Sensitivity Index-3), and distress tolerance (Distress Tolerance Scale) contributed to the level of discomfort that participants with higher hoarding scores reported when they had to leave their possession. These results highlight the relevance of emotional processes in the hoarding disorder framework as well as underscore the importance of assessing and treating them in clinical settings.